2018
DOI: 10.1111/bmsp.12127
|View full text |Cite
|
Sign up to set email alerts
|

Numerical approximation of the observed information matrix with Oakes' identity

Abstract: An efficient and accurate numerical approximation methodology useful for obtaining the observed information matrix and subsequent asymptotic covariance matrix when fitting models with the EM algorithm is presented. The numerical approximation approach is compared to existing algorithms intended for the same purpose, and the computational benefits and accuracy of this new approach are highlighted. Instructive and real-world examples are included to demonstrate the methodology concretely, properties of the estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…Default approaches for estimating standard errors also vary across programs, and it is important for the user to choose an approach that is computationally feasible, but also reasonably accurate. Although it is outside the scope of this paper to make a particular recommendation, standard error estimation is the topic of much recent research (Tian et al, 2013;Paek and Cai, 2014;Pritikin, 2017;Chalmers, 2018).…”
Section: Results Of Fitted Modelsmentioning
confidence: 99%
“…Default approaches for estimating standard errors also vary across programs, and it is important for the user to choose an approach that is computationally feasible, but also reasonably accurate. Although it is outside the scope of this paper to make a particular recommendation, standard error estimation is the topic of much recent research (Tian et al, 2013;Paek and Cai, 2014;Pritikin, 2017;Chalmers, 2018).…”
Section: Results Of Fitted Modelsmentioning
confidence: 99%
“…Guo, Ma, and de la Torre (2017) found that with misspecified Q-matrix, the standard error of item parameters estimated using the OPG approximation can be problematic, so future research may examine their influence on the performance of the Wald test. In addition, apart from the OPG, Louis’s, and sandwich information matrices investigated in this study, future research may explore the performance of the Wald test using covariance matrix calculated in other ways, such as the Oakes’s method (Chalmers, 2018) and the numerical differential methods (Jamshidian & Jennrich, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout this paper, we utilized the observed information matrix results obtained via the Oakes identity approximation method described by Chalmers (2018a).…”
Section: Models and Estimationmentioning
confidence: 99%